Development Of Scientific Literacy-Based Adolescent Reproductive Health Flip Book For ITS PKU Muhammadiyah Surakarta Health Students - Septi Aprilia; Wijayanti, Wijayanti; Heni Purwaningsih (Jurnal EduHealth, 2024)
This study aims to develop a science literacy-based Adolescent Reproductive Health Flip Book media. This research is a type of development research (R&D) using the Borg and Gall model with four stages, namely introduction, development stage, testing and dissemination stage. In this study, the validators were material and media experts. This trial involved students and lecturers from the Midwifery and Anesthesiology Nursing Study Program of ITS PKU Muhammadiyah Surakarta in the academic year 2023/2024, with data collection methods of observation, questionnaires, interviews and tests. Qualitative descriptive techniques and descriptive statistics were used to analyze the data. The limited group trial showed a validity of 78.13%, the broad group trial showed a validity of 87.1%, and the material validation showed 88.75%. Student learning outcomes showed a higher average student post-test score of 81.75 compared to the pre-test score of 69.5. The results showed that Flip Book is a valid and effective learning tool and is suitable for use as an innovative learning media